The Sex and Race Specific Relationship between Anthropometry and Body Fat Composition Determined from Computed Tomography: Evidence from the Multi-Ethnic Study of Atherosclerosis. - Morgana Mongraw-Chaffin; Sherita Hill Golden; Matthew A Allison; Jingzhong Ding; Pamela Ouyang; Pamela J Schreiner; Moyses Szklo; Mark Woodward; Jeffery Hunter Young; Cheryl A M Anderson (PLoS ONE)
Background Few studies have investigated the relationship of anthropometric measurements with computed tomography (CT) body fat composition, and even fewer determined if these relationships differ by sex and race. Methods CT scans from 1,851 participants in the population based Multi-Ethnic Study of Atherosclerosis were assessed for visceral and subcutaneous fat areas by semi-automated segmentation of body compartments. Regression models were used to investigate relationships for anthropometry with visceral and subcutaneous fat separately by sex and race/ethnicity. Results Participants were 50% female, 41% Caucasian, 13% Asian, 21% African American, and 25% Hispanic. For visceral fat, the positive relationship with weight (p = 0.028), waist circumference (p<0.001), waist to hip ratio (p<0.001), and waist to height ratio (p = 0.05) differed by sex, with a steeper slope for men. That is, across the range of these anthropometric measures the rise in visceral fat is faster for men than for women. Additionally, there were differences by race/ethnicity in the relationship with height (p<0.001), weight (p<0.001), waist circumference (p<0.001), hip circumference (p = 0.006), and waist to hip ratio (p = 0.001) with the Hispanic group having shallower slopes. For subcutaneous fat, interaction by sex was found for all anthropometric indices at p<0.05, but not for race/ethnicity. Conclusion The relationship between anthropometry and underlying adiposity differs by sex and race/ethnicity. When anthropometry is used as a proxy for visceral fat in research, sex-specific models should be used.